MULTIVARIATE ANALYSIS OF PERFORMANCE OF JAMBI CITY HEALTH SERVICE EMPLOYEES - Rumita Ena Sari; Arnild Augina Mekarische; Shafira Ainun Hafilda (Pusat Riset dan Inovasi Nasional, 2022)
Background: Performance is a function of encouragement and expertise for a person in carrying out an obligation and work in order to have a certain degree of ability and ability. Jambi Health Department report in 2020 it was known that of the 12 types of health services in the Jambi City Health Office, there are 8 health service performances that have decreased. This research aims to analyzed the performance of employees at the Jambi City Health Office. Methods: This type of research was a quantitative research with a cross sectional research design. Total population in this research were 140 respondents with a total sample of 82 respondents. Data collected was carried out in January 2022 to March 2022. Data collected used questionnaires that had been tested for validity and reliability. Data analyzed with SPSS with multiple linear regression test. Results: Based on the results research, the final model found that employee performance = 1.709 - 0.062 age + 0,098 vision and mission + 0.355 measure of success + 0.121 satisfaction with insentive + 0.262 satisfaction with superiors + 0.109 satisfaction with colleagues. The most influential factor on employee performance was the measure of success where if you increase it 100% (1 point) then the performance will increase by 31.7%. Conclusion: The most influential factor on employee performance was measure of success where if increased by 100% (1 point) then the performance will increase by 31.7%. It is hope that employees who are expected to use time effectively, know the results that each program wants, have supporting factors in achieving success, pay attention to employee incentives, superiors must be firm in giving warnings to employees who violate, and employees increase interaction with co-workers achieved.